(untitled) (Vietnam Journal of Community Medicine, 2020)
Objectives: To determine the level of contamination of heavy metals and plant protection chemicals in cheese in Ho Chi Minh City, 2020. Subjects and methods: Select 60 most popular commercial cheese products in the study area (based on data reported by the City Food Safety Bureau). In which, 30 domestic products and 30 imported products. Evaluate the contamination level of some chemical parameters. Results and Conclusion: Lead concentration was 0.011 ± 0.007 mg / kg, arsenic concentration was 0.237 ± 0.181 mg / kg, cadmium concentration is 0.481 ± 0.371 mg / kg, Mercury concentration is 0.017 ± 0.018 mg / kg for domestic products. Lead concentration was 0.005 ± 0.007 mg / kg, Arsenic concentration was 0.099 ± 0.14 mg / kg, Cadmium concentration was 0.380 ± 0.358 mg / kg, Mercury concentration is 0.019 ± 0.018 mg / kg for the imported product. Lead concentration exceeded the permitted limit in 2/30 domestic product samples and 1/30 imported samples. Arsenic concentration exceeded the permitted limit in 1/30 of the domestic product sample. Cadmium concentration exceeded the permitted limit in 2/30 domestic product samples. Mercury concentration did not exceed the limit on all tested samples. Carbaryl concentration in domestic product samples was 25.52 ± 16.17 μg / kg, in imported product samples was 12.67 ± 14.26 μg / kg; Endosulfan concentration in domestic product samples was 4,301 ± 2,878 μg / kg, in imported products was 3.18 ± 3.40 μg / kg; Aldrin and Dieldrin concentrations in domestic product samples were 3.47 ± 2.07, in imported products was 1.94 ± 2.13 μg / kg. No sample contains plant protection chemical with concentration exceeded allowed limit for both domestic and imported products.